KEBUTUHAN MANUSIA DALAM PANDANGAN EKONOMI KAPITALIS DAN EKONOMI ISLAM - Rahmat Gunawijaya (Al-Maslahah : Jurnal Ilmu Syariah, 2017)
In Islam, consumption cannot be separated from the role of faith. Faith is an important benchmark because it gives viewpoints that tend to affect the human personality and behaviour. It strongly influences the quantity and quality of consumption in the form of material or spiritual satisfaction, which then shapes the behaviour of market consumption trend. It is certainly in contrast to the principle of the fulfillment of human needs according to a more capitalist economy on the orientation of the material to maximize the production of goods and services to meet human needs. The cornerstone of the philosophy of the capitalist is secularism, separating spiritual and material (or religion and the world) by dikotomis.